Effects of low‐dose aspirin on gastric erosions, cyclooxygenase expression and mucosal prostaglandin‐E2 do not depend on Helicobacter pylori infection - VENERITO, M.; TREIBER, G.; WEX, T.; KUESTER, D.; ROESSNER, A.; DI MARIO, F.; MALFERTHEINER, P. (Alimentary pharmacology & therapeutics, 2006)
Summary Background  The mechanisms by which Helicobacter pylori and low‐dose aspirin induce gastric damage are not completely elucidated. Aim  To evaluate the effects of low‐dose aspirin on gastric damage, mucosal prostaglandin‐E2 levels and cyclooxygenase‐enzyme expression in relation to the H. pylori status. Methods  Twenty healthy volunteers (H. pylori positive, n = 10; H. pylori negative, n = 10) received aspirin 100 mg/die for 1 week. At days 0, 1, 3 and 7, gastric mucosal lesions were studied by oesophagogastroduodenoscopy and histology. COX‐1 and COX‐2 were determined by immunohistochemistry and reverse‐transcriptase polymerase chain reaction, and mucosal prostaglandin‐E2 levels by enzyme‐linked immunosorbent assay. Nine H. pylori‐positive subjects repeated the protocol after H. pylori eradication. Results  All groups developed a similar number of erosions. COX‐1 and COX‐2 expression, as well as mucosal prostaglandin‐E2 levels were not influenced by H. pylori status and aspirin medication. Helicobacter pylori‐negative and H. pylori‐eradicated subjects who developed aspirin‐induced erosions had significant lower pre‐treatment antral prostaglandin‐E2 levels than those without erosions (3.6 ng/μg vs. 6.3 ng/μg protein and 3.6 ng/μg vs. 6.0 ng/μg protein, respectively, P < 0.01 Mann–Whitney U‐test). Conclusions  In healthy subjects, low‐dose aspirin for 1 week does neither affect cyclooxygenase expression nor mucosal prostaglandin‐E2 levels. Antral prostaglandin‐E2‐basal levels appear to be critical for development of aspirin‐induced gastric damage in subjects without H. pylori infection.